Compare the Influence of Masculinity on Gender Equality in Thailand and China - Zhang, Ziyan (Transactions on Social Science, Education and Humanities Research, 2024)
The academic definition of masculinity is a concept that encompasses men's gender temperament, gender roles, gender norms, power order, and other related aspects. The persistent presence of unequal gender regimes can be explained by the concept of hegemonic masculinity, in particular. The paper compares the masculinity of Chinese and Thai men, examining how differing societal status and national cultures influence masculinity. Both countries exhibit a lack of value for domestic work and father absence in child-rearing, reflecting a dominance of male-centric masculinity. However, China shows progress in women's economic and social status, with gender equality being a state policy. In Thailand, Brahmanism influences the perception of male superiority, leading to a feminine transformation among men. Thailand exhibits more sexual liberty, particularly accepting of transsexuality, unlike China where LGBTQ+ students face gender-based bullying. Suggestions for improvement include enhancing the educational role of fathers, promoting gender equality in Thai education and homes, and respecting children's gender expression in China. The study acknowledges limitations, notably the lack of recent data on masculinity changes in Thailand, suggesting further research in the future.